«…come uno che ha gettato via gli oggetti delle purificazioni, senza volgere gli occhi»* Liminarità e impurità nel mondo greco - Carboni, Romina (O T I V M, 2017)
The aim of this paper is to focus on some cultic features related to liminal space in the Greek world. Through the use of literary and iconographical sources, I try to analyze ritual dynamics and meanings connected to offerings for gods like Hekate, Hermes and Apollo at city gates, boundary and crossroads. Another purpose of this paper is to show the main religious prescriptions about pollution and purification in Greek religion related to liminal deity.